Synthesis of MgAl2O4: Sm3+ Nanophosphor and Its Photoluminescence, Electrochemical Sensing, and Photocatalytic Studies - S. N. Manjula; M. Chandrasekhar; M. R. Anil Kumar; Mir Waqas Alam; C. R. Ravikumar; H. C. Ananda Murthy; N. Basavaraju; H. Nagabhushana (Advances in Materials Science and Engineering)
A series of MgAl2O4: Sm3+ nanophosphors were synthesized using oxalyl dihydrazide (ODH) as fuel at low temperature. The X-ray diffraction studies revealed a crystallite size of 20 nm for the nanophosphors. The energy band gap values were found to be in the range from 4.86 to 5.42 eV. Because of distinct f–f transitions from 4F7/2 ⟶ 6P3/2 of Sm3+ ions in the host stimulated at 406 nm, the PL characteristic emission peaks of Sm3+ ions were observed between 406 and 605 nm. The optimized MgAl2O4: Sm3+ phosphors exhibited 97% colour purity and lie in the orange red to yellow area of the CIE diagram. With MgAl2O4: Sm3+ nanophosphors, novel photocatalysts for the elimination of the dye Fast orange red (FOR) have been proved to function at an excited wavelength of 493 nm in UV light. The experiment showed 97.46% dye decolorization, respectively, after 120 min irradiation. Using the carbon paste electrode in the cyclic voltammetry (CV) technique, lead was detected in 0.1N HCl solution (MCPE). The MgAl2O4: Sm3+ nanophosphors are useful sensing material for an element like lead. Finally, we conclude that the synthesized MgAl2O4: Sm3+ nanophosphors are potential candidates for multifunctional applications.